Can earlier BCG vaccination reduce early infant mortality? Study protocol for a cluster randomised trial in Guinea-Bissau - Thysen, Sanne M (BMJ Open, 2019)
INTRODUCTION: The BCG vaccine is designed to protect against tuberculosis, but the vaccine may have broader effects. In 2014, the Strategic Advisory Group of Experts on Immunization reviewed the literature on non-specific effects of BCG, and concluded that the evidence was consistent with beneficial non-specific effects and requested further randomised trials. METHODS AND ANALYSES: Within the Bandim Health Project’s urban and rural health and demographic surveillance systems, we will conduct a cluster-randomised trial in six suburban districts and 55 rural villages. Infants are enrolled at a home visit before 72 hours of life. In intervention clusters, children are vaccinated with BCG and oral polio vaccine (OPV). In control clusters, the caregivers are informed about vaccination opportunities. Using Cox-proportional hazards models, we will test whether BCG and OPV provided at a single home visit can reduce early infant mortality up to 60 days. The trial was initiated with a pilot study in Biombo region in June 2015. The trial was scaled up to full study including Oio and Cacheu regions in July 2016. The trial was expanded to include the urban study area in July 2017. ETHICS AND DISSEMINATION: BCG vaccination is delayed in many low-income settings. WHO-recommended home visits are resource demanding and vaccines are not part of the recommendation. Utilising the home visits to provide BCG and OPV may provide countries with a further incentive to introduce a single home visit. In countries, where home visits are already in place, vaccines can easily be added to reduce early infant mortality. The trial is approved by the Guinean Ethical Committee (Reference number: 0016/CNES/INASA/2015) and the Danish Ethics Committee has given its consultative approval. The results of the trial will be published in international peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT02504203; Pre-results.